The Gendered Impacts of Boomtowns: How Financial Dependence, Family, and Victimization Intersect with Hegemonic Masculinity - Charman, Madison; O'Connor, Christopher D. (International Journal of Rural Criminology, 2023)
Past research on the extraction industry has examined boomtown impacts or challenges primarily related to community cohesion, infrastructure issues and crime. However, few researchers have examined the gendered impacts of boomtowns, particularly as they relate to women. Through in-depth interviews with social service professionals working with women in boomtown settings, this article examines the gendered impacts associated with resource boomtowns. More specifically, this article explores the challenges women face in these hegemonically masculine environments. The research findings show how financial dependence, family impacts and victimization come to shape women’s lives in these settings and intersect with hegemonic masculinity. The article also discusses the implications of having the impacts of boomtowns be gendered.